Syariatisasi yang Tidak Konsisten: Penegakkan Prinsip Hukum Ekonomi Syariah pada Lembaga Keuangan Syariah Non Bank - Rizal; Ifelda Nengsih; Chitra Indah Sari; Riska Fauziah Hayati; Sri Mutia (Institut Agama Islam Negeri Curup, 2025)
This article aims to explain the inconsistency of Baitul Maal Wa Tamwil (abbreviated as BMT) in implementing Sharia principles. This is a case study research with an empirical legal approach which was conducted in LKMS BMT Almabruk Inc. (BMT Almabruk) of Tanah Datar Regency and BMT Al Fattah of Solok City. Data were obtained through interviews with BMT management and related documents from BMT. The result of study showed that firstly, Sharia compliance in fund distribution contract in the form of murabahah was divided into two: murabahah through cooperation with partners and murabahah with a wakalah contract. In the first model, Sharia implementation in Murabahah was consistent, meanwhile it was inconsistent in the second one. Similarly, it still contained the elements of usury in determining its administrative costs. Second, Sharia compliance in the fund collection contract appears to be inconsistent in mudharabah savings. Third, Sharia Supervisory Board at BMT Almabruk had been consistent in monitoring Sharia principles. On the other hand, the performance of BMT Al Fattah had been inconsistent in monitoring the Sharia principles themselves. Based on the results of the study, a new scheme needs to be found for BMT to be consistent with the principles of Sharia economic law, for instance, administrative costs are used as unit costs which are included in the acquisition cost; the implementation of Sadd adz-Dzariah concept in the merger of two contracts; the implementation of Murabahah contract is carried out only after the Wakalah contract is fully completed or the goods have become the property of BMT; and the Mudharabah contract which applies to savings that can be withdrawn at any time is replaced by Hajj savings or Umrah savings that have a fixed term.